Does a human rights-based approach to harm reduction support commercialized harm reduction? Brief research - Sircar, Neil; Fleming, Mary E.; Bialous, Stella A. (Frontiers in Public Health, 2022)
In recent years, the tobacco industry has been pushing a narrative that their newer lines of products—including electronic nicotine delivery devices—are offered in part to meet a social responsibility of providing potentially reduced-harm choices to their consumers. While some of the newer tobacco products might potentially be less harmful than combustible tobacco products, there is also significant deviation from the very concept of harm reduction when it is used for such a conspicuously commercialized purpose. The framing of commercialized tobacco harm reduction as a mere consumer preference by the industry is not clearly consistent with the core principles of harm reduction, let alone the human right to health and the highest attainable level of health. A human rights-based approach (HRBA) to harm reduction is a set of principles that frame an effort to respect and promote human rights, including the right to health. Whether the HRBA supports commercialized harm reduction requires study. We review industry materials from 2017 to 2022 to identify themes in the harm reduction narrative of the tobacco industry and analyse those themes using an HRBA to the tobacco harm reduction framework. Using this analysis, the industry's continued marketing of combustible products alongside their “potentially less harmful” products, and preference that their non-combustible products be regulated less strictly than cigarettes and cigars, adulterates the public health principles of harm reduction and undermines the right to health. We conclude that the tobacco industry's commercialized tobacco harm reduction is incompatible with a human rights-based approach to tobacco harm reduction.